Evaluation of Compacted Forage Feed on Kupang Cattle Feeding Behavior - Fensa Eka Widjaya; Despal Despal; Yuli Retnani; Rudy Priyanto; Luki Abdullah (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
Forage compact feed has the ability to cut the adaptation period of grazing cattle when transported, because they are used to consume forage. The effect of the form and type of forage formulation on the feeding behavior of cattle needs to be studied further to determine the preferences of cattle for this compact feed. This study used 36 cattle with 3 replications in each treatment. The 2 factor groups withfactorial design consisting formulation and form of feed was applied in this study. The forms of feed used in this study were wafers, pellets, dried pellets, and cubes. The formulations used in this study were formulation 1 (10% molasses, 30% indigofera leaves, 50% straw, 10% elephant grass); formulation 2 (10% molasses, 30% indigofera leaves, 60% straw); formulation 3 (10% molasses, 20% indigofera leaves, 65% straw, 5% hemp). The parameters observed in this study were eating behavior of cattle which consisted of the frequency and duration of eating, drinking, rumination, and resting. The results showed that there wasan interaction on eating frequency and cattle duration. Formulation 3 on wafer treatment had the highest feeding frequency (P<0.05). Formulation 1 on wafer treatment had the highest duration of rumination (P<0.05). In the conclusion, Formulation 1 and 3 with wafer shape showed the best behavior for eating.